The judgment of Maria in Matricide without example, by Camilo Castelo Branco - Parra Filho, Raphael Hernandes [UNESP]; Pavanelo, Luciene Marie [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2023)
The purpose of this article is to present an analysis of the third edition of Maria, nao me mates, que sou tua mae!, a cordel pamphlet which first edition was published by Camilo Castelo Branco in 1848. Despite being a great public success at the time, the work received little attention from specialized critics, being mentioned only as the author's fist narrative. In this paper, we will highlight some specificities of the third edition of the work, entitled Matricidio sem exemplo, today practically unknown.
Keywords: Narrative; Crime; Matricide; Camilo Castelo Branco